Imperfect collusion in an asymmetric duopoly - Escrihuela-Villar, Marc; Gutiérrez-Hita, Carlos (Estudios de Economía, 2018)
Using the coefficient of cooperation, we analyse the effect of cost asymmetries on collusive agreements when firms are able to coordinate on distinct output levels than the unrestricted joint profit maximization outcome. In this context, we first investigate the extent to which collusive agreements are feasible. Secondly, we focus on collusion sustainability in an infinitely repeated game. We show that, regardless of the degree of cost asymmetry, at least some collusion is always sustainable. Finally, the degree of collusion is also endogeneised to show that cooperation has an upper bound determined by the most inefficient firm.